Citocinas pró-inflamatórias em ratos experimentalmente infectados por Trypanosoma evansi - Paim, Francine Chimelo (2011)
The aim of this study was to measure the levels of interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), interleukin 1 (IL-1) and interleukin 6 (IL-6) in serum of rats experimentally infected with Trypanosoma evansi and to correlate with the hematological parameters. Seventy-six rats (Wistar) were divided into two groups. Group C (control) composed of twenty-eight non-inoculated rats distributed in four subgroups with seven animals each (C3, C5, C10 and C20), which received 0.2 mL saline by intraperitoneally. The group T (infected) formed of forty-eight rats was inoculated intraperitoneally with cryopreserved blood containing 1x106 trypomastigotes per animal. These, eight animals died between 5th -7th days post-infection. The remaining animals were divided into four subgroups with ten animals (T3, T5, T10 and T20) according to parasitemia degree. The blood samples were collected by cardiac puncture at the day 3 (C3, T3), 5 (C5, T5), 10 (C10, T10) and 20 (C20, T20) post infection (pi) to perform the complete blood count and determination of IFN-γ, TNF-α, IL-1 and IL-6 levels using an ELISA quantitative sandwich. Immediately after collection the animals were euthanized. The levels of all measured cytokines increased significantly (P < 0.01) in infected animals compared to the controls. T. evansi infection in rats caused an increase in serum IFN-γ, TNF-α, IL-1 and IL-6 and this increase was observed during the whole experimental infection. In addition, the increase in the cytokine levels was concomitant and directly correlated with parasitemia and anemia development at the parasitemia peak. These results suggest a synergism between these cytokines contributing to the development of anemia and the regulation of the immune response against the parasite.